2022
DOI: 10.1371/journal.pone.0273016
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19’s impacts on the scope, effectiveness, and interaction characteristics of online learning: A social network analysis

Abstract: The COVID-19 outbreak brought online learning to the forefront of education. Scholars have conducted many studies on online learning during the pandemic, but only a few have performed quantitative comparative analyses of students’ online learning behavior before and after the outbreak. We collected review data from China’s massive open online course platform called icourse.163 and performed social network analysis on 15 courses to explore courses’ interaction characteristics before, during, and after the COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…The results of the present study are further strengthened with findings from an earlier study, which showed that all the changes made during the COVID-19 pandemic showed learning effectiveness [ 3 ]. Another study showed that the network scale of most courses did not change significantly, giving evidence that the COVID-19 pandemic did not notably change the scale of course interaction [ 45 ]. Interestingly, even before the COVID-19 pandemic, a research study showed that online or blended learning for teaching clinical skills is equally effective and similar to traditional means, and it may even benefit the teaching of clinical skills in undergraduate nursing curriculum [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study are further strengthened with findings from an earlier study, which showed that all the changes made during the COVID-19 pandemic showed learning effectiveness [ 3 ]. Another study showed that the network scale of most courses did not change significantly, giving evidence that the COVID-19 pandemic did not notably change the scale of course interaction [ 45 ]. Interestingly, even before the COVID-19 pandemic, a research study showed that online or blended learning for teaching clinical skills is equally effective and similar to traditional means, and it may even benefit the teaching of clinical skills in undergraduate nursing curriculum [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the reduction in basic sciences episodes may reflect the nature of social sciences lending more favorably to the conversational style of podcasts and digital modalities overall. 48 There are several strengths to our study. Comprehensive keywords and thorough inclusion criteria were used, including only English-language podcasts with accessible audio, more than one episode, and the majority of content related to ophthalmology.…”
Section: Discussionmentioning
confidence: 99%
“…Learning support services include information, resources, personnel, and related interactive facilities. These resources cater to the diverse needs of students and effectively guide, assist, and promote their independent learning, collaborative learning, and holistic development [ 58 ]. Student support services must be integral to the education system to meet students’ needs and expectations [ 59 ].…”
Section: Discussionmentioning
confidence: 99%